Incisional Hernia Classification Predicts Wound Complications Two Years after Repair. Issue 7 (July 2015) - Baucom, Rebeccah B.; Ousley, Jenny M.; Oyefule, Omobolanle O.; Stewart, Melissa K.; Holzman, Michael D.; Sharp, Kenneth W.; Poulose, Benjamin K.
Classification of ventral hernias (VHs) into categories that impact surgical outcome is not well defined. The European Hernia Society (EHS) classification divides ventral incisional hernias by midline or lateral location. This study aimed to determine whether EHS classification is associated with wound complications after VH repair, indicated by surgical site occurrences (SSOs). A retrospective cohort study of patients who underwent VH repair at a tertiary referral center between July 1, 2005 and May 30, 2012, was performed. EHS classification, comorbidities, and operative details were determined. Primary outcome was SSO within two years, defined as an infection, wound dehiscence, seroma, or enterocutaneous fistula. There were 538 patients included, and 51.5 per cent were female, with a mean age of 54.2 ± 12.4 years and a mean body mass index of 32.4 ± 8.6 kg/m 2 . Most patients had midline hernias (87.0%, n = 468). There were 47 patients (8.7%) who had a lateral hernia, and 23 patients (4.3%) whose repair included both midline and lateral components. Overall rate of SSO was 39 per cent (n = 211) within two years. The rate of SSO by VH location was: 39 per cent (n = 183) for midline, 23 per cent (n = 11) for lateral, and 74 per cent (n = 17) for VHs with midline and lateral components ( P = <0.001). Patients whose midline hernia spanned more than one EHS category also had a higher rate of SSOs ( P = 0.001). VHs are often described by transverse dimension alone, but a more descriptive classification system offers a richness that correlates with outcomes.